(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The problem of developing lingvomethodological thinking remains relevant today. Lingvo-methodical thinking is a complex thinking activity of the pedagogue aimed at selecting, adapting and updating language teaching methods.This article sheds light on the problem of lingvodidactic thinking in modern science and explores various interpretations of this concept.